Samernas folkhögskola och de samiska språken 1942–1990 - Hansson, Johan (Umeå University Library, 2016)
The Sami folk high school and the Sami languages 1942–1990The Swedish Mission Society – SMS (Svenska missionssällskapet – SMS), wanted to improve the opportunities’ for Sami youth in Sweden and therefore they started a folk high school (folkhögskola) for the Sami in 1942. One of the aims of SMS was to help the Sámi to preserve and develop the Sami culture and languages. Over time Sami themes, the languages being one, became more prominent at the school. However some of the problems regarding the language teaching remained: the students wanted to learn different Sami languages, their linguistic skills varied a lot, and there was not that many students who wanted to learn Sami. Despite these problems, the teaching improved over the years and the Sami folk high school remained important for the Sami people during the researched period.